ART OF PREPARATION OF MOUNTED SKELETON OF LABORATORY ANIMAL SPRAGUE DAWLEY RAT (RATTUS NORVEGICUS) - Ladukar, Neeta; Patil, D Y (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Sprague dawley rat was died and brought to the laboratory. Macerated bones were procured. Design of skeleton was prepared and all the bones and joints were assembled as per the design. Vertical rod, horizontal rod and platform were prepared. The mounted skeleton was prepared to understand the topographic position of bony features, splanchnic organs, site of intra-cardiac puncture, dorsal veins and site of surgical techniques.
Keywords: Laboratory animals; Mounted skeleton; Sprague Dawley rat